The Quality of life of Educational Personnel at Phranakhon Si Ayutthaya Rajabhat University - Tarawood, Vorawood; Rungtaweechai, Rungtaweechai (Mahachula Academic Journal, 2026)
The objectives of this research were (1) to investigate the quality of life of educational personnel at Phra Nakhon Si Ayutthaya Rajabhat University (2) to investigate the physical activity development was to investigate the quality of life of educational personnel for health of educational personnel. The research instruments used were the Quality of Life questionnaire (SF-36) and semi-structured interviews regarding office syndrome symptoms that affect the quality of life of the personnel. The research findings revealed that among those scoring below the benchmark, the physical component scale (PCS) dimension, specifically the dimension of perceived overall health (GH), had the highest score below the benchmark at 28.57%. This was followed by the bodily pain (BP) dimension at 24.50%. The mental and emotional component scale (MCS) which was Social Functioning (SF), also showed the highest score below the benchmark with a score 33.88%. This was followed by Mental Health (MH), with a score 15.51% below the benchmark. Furthermore, both genders had lower average scores than average in the Social Functioning (SF) dimension, with females scoring 45.86 and males scoring 46.36 below the benchmark. Compared to last year, 32.58% of men perceived their health as worse, while 61.24% of women felt the same. Regarding their current lifestyle, participants reported feeling discouraged, bored, pressured, unmotivated, and exhausted at work. These problems affected their work and daily routines.